1988
DOI: 10.1346/ccmn.1988.0360203
|View full text |Cite
|
Sign up to set email alerts
|

New Data and a Revised Structural Model for Ferrihydrite

Abstract: Abstract--Synthetic 2-line and 6-line ferrihydrite samples prepared from ferric nitrate solutions have the bulk compositions Fe4(O,OH,H20)12 and Fe4.6(O,OH,H20)lZ, respectively. The composition depends on crystal size, which averages 20/~ for 2-line and 35/k for 6-line ferrihydrite. X-ray absorption edge spectra indicate the presence of tetrahedral Fe 3+, a conclusion supported by heating experiments which show the development of maghemite after heating to 300~ in the presence of N2, followed by the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
215
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(244 citation statements)
references
References 45 publications
28
215
1
Order By: Relevance
“…Thus, the crumpling feature of Si-0 in Figure 2f suggests that the lepidocrocite forms rapidly under the present cultivation conditions in Si-0 and -11.5. Similar to a finding by Eggleton et al [26], we observed a very broad peak at 30°-40° (black triangle), which plausibly was derived from 2-line ferrihydrite (2Fh), for Si-11.5 to Si-300. Based on these patterns, the sheath texture in Si-0 and -11.5 was composed of a single phase of poorly crystalline lepidocrocite and a mixed phase of 2Fh and poorly crystalline lepidocrocite, respectively.…”
Section: Ed/xrd-results and Crystallinity Of Sheathssupporting
confidence: 90%
“…Thus, the crumpling feature of Si-0 in Figure 2f suggests that the lepidocrocite forms rapidly under the present cultivation conditions in Si-0 and -11.5. Similar to a finding by Eggleton et al [26], we observed a very broad peak at 30°-40° (black triangle), which plausibly was derived from 2-line ferrihydrite (2Fh), for Si-11.5 to Si-300. Based on these patterns, the sheath texture in Si-0 and -11.5 was composed of a single phase of poorly crystalline lepidocrocite and a mixed phase of 2Fh and poorly crystalline lepidocrocite, respectively.…”
Section: Ed/xrd-results and Crystallinity Of Sheathssupporting
confidence: 90%
“…A total mass loss of FHYD-000 is 21.28 mass% and remains similar for all the samples studied. The losses are comparable with earlier measurements of both synthetic [5,17,35,37,39] and natural ferrihydrites [16,25,49], but are explicitly higher than theoretical water content (*17 mass%), due to a high amounts of physisorbed water. A bend on DTA curves of low-Si samples at ca.…”
Section: Thermal Studiessupporting
confidence: 88%
“…These ions affect ferrihydrite composition, surface chemistry, reactivity and sorption properties [14,[17][18][19][20][21][22]. Silicate, the most important impurity, lowers crystallinity of this nanomineral and modifies its morphology, magnetic ordering and solubility [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], though the ferrihydrite structure itself is not directly altered [30]. Reducing crystallinity has been thought to result from the formation of soluble Fe-Si complexes during the oxyhydroxide precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibits all the features of the deficient spinel structure of oxidized magnetite; however, because of the process of formation, long range ordering may still be poor, significant hydroxylation is probably retained, and tetrahedral sites may be partly vacant. Pure ferrihydrite is well known to be a phase which shows variable degrees of hydration and ordering, (e.g., Chukhrov et al, 1973;Eggleton and Fitzpatrick, 1988). The "m" species might actually be an additional variety, with prevailing ccp ordering.…”
Section: Discussionmentioning
confidence: 99%